2023
DOI: 10.1093/chemse/bjad007
|View full text |Cite
|
Sign up to set email alerts
|

No significant salt or sweet taste preference or sensitivity differences following ad libitum consumption of ultra-processed and unprocessed diets: a randomized controlled pilot study

Abstract: Ultra-processed food consumption has increased world-wide, yet little is known about the potential links with taste preference and sensitivity. This exploratory study aimed to (i) compare sweet and salty taste detection thresholds and preferences following consumption of ultra-processed and unprocessed diets, (ii) investigate whether sweet and salty taste sensitivity and preference were associated with taste-substrates (i.e. sodium and sugar) and ad libitum nutrient intake, and (iii) examine associations of ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…However, only BMI had a positive correlation with salt intake. The positive correlation found between salt intake and BMI, albeit expected [27], is of great concern since obesity and high salt intake are two common risk factors strongly associated with non-communicable diseases, such as hypertension even in young adults [28].…”
Section: Discussionmentioning
confidence: 98%
“…However, only BMI had a positive correlation with salt intake. The positive correlation found between salt intake and BMI, albeit expected [27], is of great concern since obesity and high salt intake are two common risk factors strongly associated with non-communicable diseases, such as hypertension even in young adults [28].…”
Section: Discussionmentioning
confidence: 98%
“…Among these participants, a higher intake of oils and fats, potatoes and tubers and higher relative abundance of Oscillospiraceae were found. Although some authors have found an association between increased relative abundances of this microbial family and depression, the evidence in the literature is still inconsistent [ 81 , 82 , 83 , 84 ], and depression may remain constant after dietary interventions, according to previous research [ 85 ]. In all groups of individuals (LC and HC) an improvement in taste discrimination, both sweet and salty, was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The greater EIR of UPFs may also generate a greater food reward that alters gut-brain signalling, flavour-nutrient conditioning and food preference [ 77 ]. However, an exploratory study of Hall et al found no difference in sweet or salty taste preference or taste detection thresholds after UPF or MPF diets [ 78 ]. Sweet or salty taste preference or detection was unrelated to ad libitum sugar or salt intake on either diet [ 78 ].…”
Section: Mechanisms: What Drives the Effect?mentioning
confidence: 99%
“…However, an exploratory study of Hall et al found no difference in sweet or salty taste preference or taste detection thresholds after UPF or MPF diets [ 78 ]. Sweet or salty taste preference or detection was unrelated to ad libitum sugar or salt intake on either diet [ 78 ].…”
Section: Mechanisms: What Drives the Effect?mentioning
confidence: 99%